EFFECT OF COMMERCIAL RATION REPLACEMENT WITH BREAD WASTE ON THE INTERNAL ORGANS OF THE SUPERIOR VILLAGE CHICKEN FOR BALITNAK (KUB) - A., Putri; Siti, N. W.; Puspani, E. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
Bread waste is bread that is no longer fit for human consumption because it has passed the expiration date. This study aims to determine the effect of replacing commercial rations with bread waste on the internal organs of superior Kampung chicken for balitnak (KUB). This research was conducted from July to September 2021 at a farm located on Jalan Banjar Tengah Gulingan, Gulingan Village, Mengwi District, Badung Regency for 8 weeks. The research design used was a Completely Randomized Design (CRD) consisting of 3 treatment and 5 replications and each replication contained 2 KUB chicken With one week old homogenized weight. The treatments were superior village chicken for Balitnak (KUB) which were given commercial rations 511 without bread waste (P0), superior Kampung chicken for Balitnak (KUB) which were given 75% commercial rations 511 + 25% waste of bread To replace most commercial rations 511 (P1), and superior Kampung chicken for Balitnak (KUB) were given 50% commercial rations 511 + 50% waste of bread To replace most commercial rations 511 (P2). The variables observed were the percentage of heart, percentage of liver, percentage of kidney, percentage of spleen, percentage of bile, percentage of proventiculus, percentage of ventriculus. The results showed that the replacement of 25% and 50% of commercial rations with bread waste significantly (P<0.05) increased the percentage of liver. But it was not significantly different (P>0.05) on the percentage of heart, percentage of spleen, percentage of kidney, percentage of bile, percentage of proventiculus and percentage of ventriculus. Based on the results of the study, it can be concluded that the replacement of commercial 511 rations by using bread waste as much as 25%-50%, increases the percentage of liver, but gives the same results on the percentage of heart, percentage of spleen, percentage of kidney, percentage of bile, percentage of proventiculus and percentage of ventriculus. Keyword : KUB chickens, percentage of internal organs, bread waste.